Impairments of social interaction in a valproic acid model in mice - Ukezono, Masatoshi; Kasahara, Yoshiyuki; Yoshida, Chihiro; Murakami, Yuki; Okada, Takashi; Takano, Yuji (Frontiers in Behavioral Neuroscience, 2024)
Background A rodent autism spectrum disorder (ASD) model based on prenatal exposure to valproic acid (VPA) is widely recognized as a prominent model. Social behavior in rodent ASD models has primarily been evaluated through a three-chamber approach test. However, in this study, we focused on social attention in the VPA model of ASD. Methods In male C57BL/6 J mice, attentional behaviors toward conspecifics were examined through reaching tasks around 9–11 weeks of age. On embryonic day 12.5, pregnant mice underwent a subcutaneous injection of 600 mg/kg VPA sodium salt dissolved in 0.9% saline solution (VPA group) or saline solution alone (Sal group) into their neck fat. Thirty-six mice—nine each in the VPA and saline groups, and 18 partners—underwent training in reaching behavior. Subsequently, we examined whether the VPA or Sal group demonstrated focused attention toward their partners during reaching tasks. A two-way analysis of variance (ANOVA) (condition [VPA/Sal] × situation [face-to-face (attention)/not paying attention (not attention)]) was conducted on the average success rate of the situation. Additionally, we measured the duration of sniffing behavior between pairs of mice in an open field twice in total at 4 and 8 weeks of age before reaching task. The pairs were constructed by pairing a VPA or Sal group mouse with its partner, with the objective of facilitating initial encounters between the mice. A one-way ANOVA was conducted on the average duration of sniffing behavior data from 4 weeks and a second one-way ANOVA on data from 8 weeks. Results The analysis revealed a significant interaction between condition and situation in the reaching task [F (1, 28) = 6.75, p = 0.015, ηp2 = 0.19]. The simple main effect test exhibited that the “not paying attention” rate was significantly higher than that of the “face-to-face” in the VPA group (p < 0.01). The results revealed a not significant difference in the average duration of sniffing behavior at 4 weeks [F (3, 32) = 2.71, p = 0.06, n.s., ηp2 = 0.20], but significant difference at 8 weeks [F (3, 32) = 4.12, p < 0.05, ηp2 = 0.28]. Multiple comparisons using the Bonferroni method revealed significant differences in the sniffing duration at 8 weeks between from the partner toward the VPA mouse and from the partner toward the Sal mouse (p < 0.05). Conclusion The VPA rodent model of ASD exhibited differences in social attention compared to the saline group. By focusing on social attention and exploring various ASD models, insights can be gained from the neural mechanisms underlying gaze abnormalities during social interaction in individuals with ASD.